SURVEY BOAT PROTOTYPE DESIGN FOR REMOTE AREA - Furqon, Muhammad Tanzil; Kadhafi, Muammar; Sunardi, Sunardi; Rijal, Seftiawan Samsu; Tsani, Muhammad Dafa'anh Murya (Directorate of Research and Community Service (DRPM), 2021)
The water survey activities in remote areas have many challenges, such as cost, transportation to location, access to the location, boat for water survey, manpower, and other factors. This research proposes the method of water survey to overcome the difficulties encountered in surveying in remote areas. The mini boat prototype was designed and fabricated by using a control system to operate in the water. The propulsion power prediction was carried out, by comparison, the similarity to the fullscale ships with 9.5 knots of velocity. Furthermore, the wave-making resistance was simulated by software and confirmed by the trial. The trial has shown that the boat was going well on the water and the measurement equipment in a safe condition.